Development of learning media for physical education (PE) materials on sexually transmitted diseases using google sites - Ate Maskar; Suriani Sari; Muhammad Suhairi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
This study addresses the limited use of interactive digital learning media in teaching sexually transmitted diseases (STDs) within Physical Education, Sports, and Health (PJOK) at the senior high school level, which often leads to low student engagement and insufficient understanding of reproductive health concepts. The study aims to develop Google Sites-based learning media, test its feasibility, and analyze teacher and student responses to its implementation.This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation, teacher assessments, small-scale student trials (12 students), large-scale trials (40 students), teacher responses (37 teachers), as well as pre-test and post-test evaluations involving 44 students with a control group.The results show that the developed learning media achieved a very high level of feasibility, with validation scores of 96% from material experts, 89% from learning experts, and 98% from media experts, all categorized as very good. Student responses were also highly positive, with 90% in the small-scale trial and 94% in the large-scale trial, while teacher responses from PJOK MGMP in public senior high schools in Sambas Regency reached 98%, all within the very good category. In addition, student learning outcomes increased by 28.73% based on pre-test and post-test results.These findings indicate that Google Sites-based learning media is feasible and effective in improving student engagement and understanding of STD materials. This study contributes to the integration of digital technology in PJOK learning and highlights the importance of interactive media in delivering sensitive health topics. F